Holistic Facial Composite Construction and Subsequent Lineup Identification Accuracy: Comparing Adults and Children. Issue 1 (2nd January 2016) - Davis, Josh P.; Thorniley, Sarah; Gibson, Stuart; Solomon, Chris
ABSTRACT: When the police have no suspect, they may ask an eyewitness to construct a facial composite of that suspect from memory. Faces are primarily processed holistically, and recently developed computerized holistic facial composite systems (e.g., EFIT-V) have been designed to match these processes. The reported research compared children aged 6–11 years with adults on their ability to construct a recognizable EFIT-V composite. Adult constructor's EFIT-Vs received significantly higher composite-suspect likeness ratings from assessors than children's, although there were some notable exceptions. In comparison to adults, the child constructors also overestimated the composite-suspect likeness of their own EFIT-Vs. In a second phase, there were no differences between adult controls and constructors in correct identification rates from video lineups. However, correct suspect identification rates by child constructors were lower than those of child controls, suggesting that a child's memory for the suspect can be adversely influenced by composite construction. Nevertheless, all child constructors coped with the demands of the EFIT-V system, and the implications for research, theory, and the criminal justice system practice are discussed.